Iridoid glycosides and lignans from the fruits of Gardenia jasminoides Eills. (October 2021) - Cao, Yan-Gang; Ren, Ying-Jie; Liu, Yan-Ling; Wang, Meng-Na; He, Chen; Chen, Xu; Fan, Xi-Ling; Zhang, Yan-Li; Hao, Zhi-You; Li, Hong-Wei; Zheng, Xiao-Ke; Feng, Wei-Sheng
Abstract: Four previously undescribed iridoid glycosides, including two bis-iridoid glycosides, and three undescribed lignans, together with 16 known analogues, were isolated from the fruits of Gardenia jasminoides Eills. Their structures were elucidated on basis of spectroscopic methods, and the absolute configurations of three of the unknown compounds were determined by interpretation of their electronic circular dichroic (ECD) and [α] 20 D data. The α -glucosidase inhibitory effects of the isolated compounds were evaluated and all the compounds exhibited slightly inhibitory activity with the values of IC50 greater than 50 μ M. Graphical abstract: Seven undescribed compounds, including four iridoid glycosides and three lignans, were isolated from the fruits of Gardenia jasminoides Eills. Image 1 Highlights: Seven undescribed compounds were isolated from the fruits of G. jasminoides. Their structures were elucidated by NMR and mass spectrometry. The absolute configurations were deduced by interpretation of ECD and [α] 20 D data. The α -glucosidase inhibitory effects of all the isolated compounds were evaluated.